In-situ facile synthesis of heterostructural Co||MnCo2O4.5/NC with active oxygen vacancies and its bifunctional electrocatalysis for oxygen reduction and oxygen evolution reaction. (1st August 2022) - Zhang, Xiaofeng; Cai, Jiannan; Ye, Yanzhu; Shi, Yuande; Lin, Shen
Abstract: A potential non-noble metal oxide catalyst with its low-cost and efficient catalytic ability attract increasing attention. In this paper, a highly efficient bifunctional electrocatalyst Co||MnCo2 O4.5 /NC with heterostructure and oxygen vacancies is prepared utilizing solid reaction in-situ . The optimal catalyst is obtained at 650 °C with the mass ratio (1:8) of MnCo2 O4.5 and Dicyandiamide (DCD). It shows excellent electrocatalytic activity for oxygen reduction reaction (ORR) with high half-wave potential (0.81 V) and limit current density (6.22 mA cm −2 ), which is better than that of the commercial 20% Pt/C(0.81 V, 5.52 mA cm −2 ). At the same time, it also exhibits superior electrocatalytic activity for oxygen evolution reaction (OER) with low overpotential (330 mV) and a faster dynamics process. The superior electrocatalytic properties may be resulted from the presence of heterostructure and increasing ratio of oxygen vacancies, which helps to the rapid transfer of electrons and creates more active sites. Moreover, the self-generated N-doped carbon provides high conductivity of the as-prepared Co||MnCo2 O4.5 /NC composite. It can be seen that the application of interface engineering technologies is useful for improving the performance of the catalyst, providing an effective and facile synthesis strategy for non-noble metal catalyst. Highlights: The Co||MnCo2 O4.5 /NC was prepared based on spinel MnCo2 O4.5 using solid phase reaction in situ. The Co||MnCo2 O4.5 /NC has the dual characteristic of the heterostructure and more oxygen vacancies. The Co||MnCo2 O4.5 /NC presents excellent difunctional electrocatalytic properties toward ORR and OER. The zinc-air battery using Co||MnCo2 O4.5 /NC as a catalyst shows outstanding energy density and extraordinary stability.